2014
DOI: 10.2105/ajph.2013.301706
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Barriers and Facilitators to Minority Research Participation Among African Americans, Latinos, Asian Americans, and Pacific Islanders

Abstract: To assess the experienced or perceived barriers and facilitators to health research participation for major US racial/ethnic minority populations, we conducted a systematic review of qualitative and quantitative studies from a search on PubMed and Web of Science from January 2000 to December 2011. With 44 articles included in the review, we found distinct and shared barriers and facilitators. Despite different expressions of mistrust, all groups represented in these studies were willing to participate for altr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

51
1,325
7
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,227 publications
(1,385 citation statements)
references
References 104 publications
51
1,325
7
2
Order By: Relevance
“…Minority populations often have limited access to specialty care centers that serve as referral sources for clinical studies, resulting in a lack of an effective referral base [30]. Other barriers include, but are not limited to, fears of exploitation in medical research [31], financial constraints [32], competing demands of time, lack of access to information and comprehension about research, unique cultural and linguistic differences, fears of unintended outcomes, stigmatization, and health care discrimination [31]. Highly feasible changes can increase minority participation despite the challenges described.…”
Section: Barriers To Diversify Research Need Concerted Attentionmentioning
confidence: 99%
“…Minority populations often have limited access to specialty care centers that serve as referral sources for clinical studies, resulting in a lack of an effective referral base [30]. Other barriers include, but are not limited to, fears of exploitation in medical research [31], financial constraints [32], competing demands of time, lack of access to information and comprehension about research, unique cultural and linguistic differences, fears of unintended outcomes, stigmatization, and health care discrimination [31]. Highly feasible changes can increase minority participation despite the challenges described.…”
Section: Barriers To Diversify Research Need Concerted Attentionmentioning
confidence: 99%
“…[1,7] Studies on Asian Americans have shown evidence of cultural differences in belief and attitude, [9,10] healthcare decision-making [11,12] and perception regarding clinical trial participation. [1,[13][14][15][16][17][18][19] Despite growing body of findings related to clinical trial participation, enrollment into clinical trials from Asian Americans remains low. [8] This paper aims to describe findings from a pilot study on barriers, promoters of and recommendations for cancer clinical trial participation among Chinese, Filipino and Hmong Americans.…”
Section: Introductionmentioning
confidence: 99%
“…These challenges include people's limited understanding about genetics, genomics, and clinical research; people's perceptions and beliefs regarding utility of genetic testing; people's distrust in the research process and in researchers K. C.-P. and R. S. contributed equally to this work. related to history of discrimination by medical personnel and researchers; and logistical barriers such as language, time, access, and simply not being asked to participate, which can all negatively influence community members' participation (George et al 2014;Hartz et al 2011;Millon Underwood et al 2013;Rotimi and Marshall 2010). Novel approaches that address these challenges have the potential to increase community participation in genomic-based research.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, these ethical concerns have led researchers to consider a variety of processes to obtain community input into genomic research and increase community interest in potential results (George et al 2014;Green et al 2011;Millon Underwood et al 2013;Skinner et al 2015;Yu J-H and Burke W 2012). These processes have included conducting community interviews, focus groups, and rapid ethnographic assessments (Skinner et al 2015;Tindana et al 2012) to identify perceptions and barriers to participate in community-based genetic studies; and working with communities through community advisory boards (Quinn 2004), community fora (Mascalzoni et al 2008) and community consultations (Dickert and Sugarman 2005) to increase engagement of community members in conducting genomic studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation